THE INFLUENCE OF VILLAGE EQUIPMENT, ORGANIZATIONAL COMMITMENT, COMMUNITY PARTICIPATION AND THE USE OF INFORMATION TECHNOLOGY ON THE ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT IN HULU SUNGAI TENGAH DISTRICT - Norefansyah Norefansyah (DIA: Jurnal Administrasi Publik, 2024)
Influence village apparatus competence, organizational commitment, community participation and the use of information technology on village fund management accountability in the Hulu Sungai Tengah district. This type of research is quantitative research using primary data. The population used was 230 people, and the sample was village officials in the Hulu Sungai Tengah district consisting of the village secretary, head of financial affairs, head of general affairs and planning, head of the government section and head of the welfare and service section, data collection method using a questionnaire. The results showed that the competency variables of village officials and the use of information technology had a significant influence on the accountability of managing village funds in Hulu Sungai Tengah District, then the variables of organizational commitment and community participation had no effect on the accountability of managing village funds in Hulu Sungai Tengah District.